Effect of replacement of sugarcane by oilseed press cakes in greenhouse gases and volatile fatty acids production in vitro. - MOREIRA, M. N. (2016)
Abstract This study aimed to evaluate the production of methane, carbon dioxide, and volatile fatty acids and changes in ruminal pH in vitro with oilseed press cakes inclusion, such as, cottonseed, sunflower, castor bean, moringa and jatropha at four different levels (0, 30, 50 and 70%) in replacement to the sugarcane in ruminant feeding using semi-automated in vitro technique. The byproduct that produced less CO2 was cottonseed cake (p = 0.0059). The cakes that produced the least amount of CH4 were moringa at 70% (p < 0.05) and cottonseed at 70% levels (p < 0.0001). The cakes that had the highest increases in VFAs were cottonseed and castor (p < 0.0001). Additionally, greater pH was moringa at 70% and cottonseed at 50% levels (p < 0.0001). The greater acetate concentration was 70% cottonseed cake, propionate concentration with 30% cottonseed and butyrate concentration with 50% moringa in sugarcane replace. At the 70% level, the moringa cake displayed the highest decreases in methane production and reduction in energy loss. At the 50% substitution level, the cottonseed cake is the most suitable replacement for sugarcane in order to reduce the production of greenhouse gases.